Virtual Reality System Controlled by Embedded Artificial Intelligence for Supporting Phobia Treatment - Jambo, Claudio H. M.; Werneck, Vera Maria B.; da Costa, Rosa Maria E. Moreira (Journal of the Brazilian Computer Society, 2024)
In recent years, the health area has received technological contributions that provide support for diagnostic practices, monitoring, and treatment of different disorders and diseases, mainly combining various techniques of Artificial Intelligence, Virtual Reality, and Mobile Computing. There are many challenges to integrating these technologies and providing solutions that consider the automation of processes, the simplification of interaction between professionals and patients, the low price of equipment, the individualization of use, mobility, and the use of Artificial Intelligence strategies. Aiming to overcome the limitations of two previous works, which applied technological combinations in the desensitization of stress and phobias, this work aims to develop a technological combination that integrates an autonomous and low-cost virtual environment, with multi-agent control and natural language communication support, to be used in the Treatment by Exposure in Virtual Environments - VRET in the area of Clinical Psychology, more specifically related to Anxiety Disorders. Low-cost virtual reality glasses were used, with visualization on a smartphone. The prototype, called PhobIA 3DS, is controlled by multi-agents that have modules for capturing physiological signals (heart rate); uses natural language to obtain the level of anxiety perceived by the patient; considers these two pieces of information in a Fuzzy system, which, in turn, generates a response on the calculated level of anxiety; and controls and changes the display of specific scenarios for each level of anxiety. Finally, the system was evaluated by a group of 6 experienced psychologists to verify aspects of the interface, relevance, and usability. The data obtained by the evaluation showed positive results and good prospects for using the system in real activities. As a contribution, this work created an integration of AI technologies in an ESP32 microcontroller connected to a smartphone and attached to low-cost goggles. This combination of technics opens perspectives for adopting affordable technologies in phobia treatments.